Laminate and resin film

A laminate with a resin layer having regions of varying elastic moduli addresses issues of non-uniformity and peeling in hard coat layer transfer, ensuring defect-free and functional hard coat application.

JP7619421B2Active Publication Date: 2025-01-22TORAY INDUSTRIES INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023190514
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-08-31
Filing Date
2023-11-08
Publication Date
2025-01-22
Estimated Expiration
2039-04-08

AI Technical Summary

Technical Problem

Existing methods for transferring a hard coat layer to molded bodies face challenges such as defects like repellency, non-uniform coating, tearing, and difficulty in peeling off the layer, particularly when applied to thin films.

Method used

A laminate structure with a resin layer having regions of varying elastic moduli, specifically regions A and B, where region B has a lower elastic modulus than region A, is designed to facilitate uniform transfer and easy peeling without impairing the functional properties of the hard coat layer.

Benefits of technology

The laminate structure reduces peeling force and ensures uniform application of the hard coat layer, preventing defects like repellency and tearing, while maintaining scratch resistance and weather resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007619421000024
    Figure 0007619421000024
  • Figure 0007619421000025
    Figure 0007619421000025
  • Figure 0007619421000026
    Figure 0007619421000026
Patent Text Reader

Abstract

To provide a laminate capable of being transferred with in-plane uniformity by hardly spoiling a function of a hard coat layer, such as scratch resistance and weather resistance, from a resin film, and not spoiling an appearance quality such as irregularity and transparency.SOLUTION: In a laminate having a release layer and a resin layer at least on one surface of a support base material in this order from a support base material side, there exists on the surface of the resin layer, an area (area B) observed by an atomic force microscope, and having a lower elastic modulus than an area (area A) with a high elastic modulus. The laminate satisfies following conditions: condition 1: the elastic modulus EB of the area B is 1,500 MPa or less; and condition 2: an average number of the areas B in 5 μm square is 50 or more and 300 or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin film and a laminate that can impart scratch resistance and various functions to other articles. [Background technology]

[0002] In general, the surfaces of plastics and metals are more susceptible to scratches than glass, and when used as products, it is required to maintain the gloss and transparency of the surface. Therefore, in plastic or metal molded bodies, a layer that imparts scratch resistance to the surface is sometimes provided. Specifically, a method of coating the surface with a high-hardness resin layer called a "hard coat" as exemplified in Non-Patent Document 1 is known. Furthermore, the hard coat layer may be used to impart functions other than scratch resistance, such as weather resistance, gas barrier properties, and blocking prevention properties, to the molded body.

[0003] The above-mentioned hard coat layer is generally formed by directly applying and curing the surface of the plastic or metal constituting the molded body, by attaching a plastic film on which a hard coat layer has been formed in advance, or by molding it integrally with the plastic or metal constituting the molded body. In addition, when direct application is impossible due to the heat resistance, processing temperature, or solvent resistance of the material constituting the molded body, or when a function other than scratch resistance, such as an optical functional layer or a design layer, is formed together, a method of forming a hard coat layer on a support substrate other than the material constituting the molded body and transferring it to the surface of the molded body is also available.

[0004] Furthermore, in order to make products thinner and to improve the freedom of product shape in electronic device applications, a method of transferring only the hard coat layer onto the surface of a molded product, instead of molding the entire hard coat film, is also being considered.

[0005] As such, as a method for transferring only the hard coat layer to a molded body, Patent Document 1 proposes a "transfer sheet having at least a release layer, a functional layer, and an adhesive layer on one side of a substrate, characterized in that the transfer sheet uses, as the main material, a silicone acrylic resin that becomes a strong hardened film by forming silicone bridges in the release layer, and uses a polydimethylsiloxane-based copolymer as the secondary material."

[0006] Patent Document 2 proposes "a transfer film comprising at least a release layer, a hard coat layer, and an adhesive layer laminated in that order on one side of a base film, wherein the release layer is an acrylic urethane resin having a long-chain alkyl group having 10 to 30 carbon atoms."

[0007] Patent Document 3 describes a hard coat transfer film in which at least a release layer and a hard coat layer made of an ultraviolet curable resin are laminated in this order on a plastic film, and the hard coat transfer film is characterized in that it satisfies all of the following conditions (A) to (C): (A) The release layer and the hard coat layer are laminated so as to be in contact with each other. (B) The release layer is a layer made of a thermosetting resin and a hydroxyl group-containing acrylate.

[0008] (C) The weight ratio of the hydroxyl group-containing acrylate to the thermosetting resin is 3 to 10% by weight." has been proposed.

[0009] Patent Document 4 proposes "a transfer foil comprising at least a substrate, a release layer provided on the substrate, and a protective layer releasably provided on the release layer, wherein the release layer comprises an actinic radiation curable resin and a thermosetting resin, and the protective layer comprises an actinic radiation curable resin." [Prior art documents] [Patent documents]

[0010] [Patent Document 1] JP 2004-034385 A [Patent Document 2] JP 2014-104705 A [Patent Document 3] JP 2014-180809 A [Patent Document 4] JP 2017-65017 A [Non-patent literature]

[0011] [Non-Patent Document 1] Plastic Hard Coating Application Technology CMC Publishing Co., Ltd. 2004 Summary of the Invention [Problem to be solved by the invention]

[0012] Thus, there are two essential problems to be solved in transferring a hard coat layer to a molded article: 1. The hard coat layer is unlikely to cause defects such as cissing on the release layer and can be formed uniformly within the surface. 2. The hard coat layer is unlikely to tear or zip when transferred to a molded body, and can be easily peeled off at the interface with the release layer. Regarding these two problems, the present inventors confirmed the technology of Patent Document 1 and found that the method described in the specification may be effective for a coating composition for an anti-reflection layer, but when applied to a coating composition for a hard coat, cissing occurs during coating, making it difficult to obtain a coating film with good quality, and thus the above problems could not be achieved.

[0013] The present inventors confirmed the techniques of Patent Documents 2 to 4, and found that the method described in the specification did indeed provide good transferability to a molded article in a system in which a thick hard coat layer, a primer layer, and an adhesive layer were laminated for a hard coat coating composition. However, when the resin layer became thin, it was not possible to peel the resin layer uniformly within the surface, and the above-mentioned problem could not be achieved.

[0014] For the reasons mentioned above, it is difficult for conventional techniques to solve the essential problems in the transfer of a hard coat layer including a functional layer. [Means for solving the problem]

[0015] Therefore, in order to solve the above-mentioned problems, the present inventors have conducted extensive research and have completed the following invention. 1. A laminate having a release layer and a resin layer, in that order from the supporting substrate side, on at least one surface of a supporting substrate, wherein, when observed with an atomic force microscope, the surface of the resin layer has a region (referred to as Region B) having a lower elastic modulus than a region (referred to as Region A) having a higher elastic modulus, and wherein the laminate satisfies the following conditions: Condition 1: Elastic modulus E of region B B is 1,500MPa or less Condition 2: The average number of regions B in a 5 μm square is 50 to 300. 2. The laminate according to 1., which satisfies the following conditions: Condition 3: Elastic modulus E of the region A A and the elastic modulus E of the region B B The difference between A -E B ) is 100MPa or more. Condition 4: The major axis radius of the region B is 25 nm or more and 250 nm or less. 3. A laminate according to 1. or 2., characterized in that, within a range of 5 nm from the surface of the resin layer, the region A contains a resin component represented by chemical formula 1, and the region B contains a resin component represented by chemical formula 2 and / or a resin component represented by chemical formula 3.

[0016] [ka]

[0017] [ka]

[0018] [ka]

[0019] R 1 is hydrogen or a methyl group, R 2 , R 3 , R 4 is one of the following (i) to (vi). (i) a substituted or unsubstituted alkylene group (ii) a substituted or unsubstituted arylene group (iii) a substituted alkylene group having an ether group, an ester group, or an amide group therein (iv) an unsubstituted alkylene group having an ether group, an ester group, or an amide group therein (v) a substituted arylene group having an ether group, an ester group, or an amide group therein (vi) an unsubstituted arylene group having an ether group, an ester group or an amide group therein 4. When observed by an atomic force microscope, the surface has a region (referred to as region B) with a lower elastic modulus than a region (referred to as region A) with a higher elastic modulus, A resin film characterized by satisfying the following conditions. Condition 1: Elastic modulus E of region B B is 1,500MPa or less Condition 2: The average number of regions B in a 5 μm square is 50 to 300. 5. The resin film according to 4., characterized in that the following conditions are satisfied: Condition 3: Elastic modulus E of the region A A and the elastic modulus E of the region B B The difference between A -E B ) is 100MPa or more. Condition 4: The major axis radius of the region B is 25 nm or more and 250 nm or less. 6. A resin film described in 4. or 5., characterized in that, within a range of 5 nm from the surface of the resin film, the region A contains a resin component represented by chemical formula 1, and the region B contains a resin component represented by chemical formula 2 and / or a resin component represented by chemical formula 3.

[0020] [ka]

[0021] [ka]

[0022] [ka]

[0023] R 1 is hydrogen or a methyl group, R 2 , R 3 , R 4 is one of the following (i) to (vi). (i) a substituted or unsubstituted alkylene group (ii) a substituted or unsubstituted arylene group (iii) a substituted alkylene group having an ether group, an ester group, or an amide group therein (iv) an unsubstituted alkylene group having an ether group, an ester group, or an amide group therein (v) a substituted arylene group having an ether group, an ester group, or an amide group therein (vi) an unsubstituted arylene group having an ether group, an ester group or an amide group therein Effect of the Invention

[0024] According to the present invention, a laminate can be obtained from a resin film, which is unlikely to impair the functions of the hard coat layer, such as scratch resistance and weather resistance, and which is unlikely to impair the appearance quality, such as unevenness and transparency, and which can be transferred uniformly within the plane.

[0025] According to the present invention, even if the resin layer formed on the release layer is a thin film, defects such as repelling are unlikely to occur in the resin layer, and further, even when it is transferred to a molded body, tearing or zipping is unlikely to occur, and the resin layer can be easily peeled off. [Brief description of the drawings]

[0026] [Figure 1] FIG. 2 is a cross-sectional view illustrating an example of the configuration of a laminate of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view illustrating an example of the configuration of a laminate of the present invention. [Diagram 3] FIG. 2 is a cross-sectional view illustrating an example of the configuration of a laminate of the present invention. [Figure 4] FIG. 2 is a cross-sectional view illustrating an example of the configuration of a laminate of the present invention. [Diagram 5] This is a conceptual diagram showing an example of the shape created by two types of regions A and B. [Figure 6] This is a conceptual diagram showing an example of the shape created by two types of regions A and B. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] The present inventors have found that the above-mentioned problems can be solved by making the surface of the resin layer satisfy certain conditions, as described in detail below.

[0028] First, as shown in Fig. 1, the laminate 1 of the present invention has a release layer 4 and a resin layer 5 on at least one surface of a support substrate 3, in this order from the support substrate side. The release layers may be on both surfaces of a support substrate 8 as shown in Fig. 2. Also, as in the laminate 12 of Fig. 3, a protective film 17 having an adhesive layer 18 may be attached to the surface of the resin layer 16 opposite to the surface in contact with the release layer 15, or as in the laminate 20 of Fig. 4, a functional layer 25 may be laminated on the surface of the resin layer 24 opposite to the surface in contact with the release layer 23.

[0029] The laminate of the present invention is characterized in that, when observed with an atomic force microscope, the surface of the resin layer has a region (referred to as region B) having a lower elastic modulus than a region (referred to as region A) having a higher elastic modulus, and further, the elastic modulus of region B is designed to be equal to or lower than a certain value, and the average number of regions B present within a field of view of 5 μm square is designed to be within a certain range.

[0030] Here, we will explain the elastic modulus measurement using an atomic force microscope and the region A and region B estimated therefrom. This measurement method is a compression test using a probe on a very small part, and measures the degree of deformation due to the pressing force. Therefore, the spatial distribution of the elastic modulus on the surface of the resin layer can be measured using a cantilever with a known spring constant. Details such as specific measurement and analysis procedures will be described in the Examples section, but for example, using the atomic force microscope shown below, the probe at the tip of the cantilever is brought into contact with the surface of the resin layer, and the force curve is measured with a pressing force of 55 nN to measure the deflection of the cantilever.

[0031] Atomic force microscope: Asylum Technology MFP-3DSA-J Cantilever: NANOSENSORS cantilever R150-NCL-10 (material: Si, spring constant: 48 N / m, tip curvature radius: 150 nm).

[0032] In this case, the spatial resolution in the in-plane direction depends on the scanning range and the number of scanning lines of the atomic force microscope, but under realistic measurement conditions, the lower limit is about 10 nm. In other words, for a minute region less than 10 nm in size, the elastic modulus is detected as average information, but as a result of verifying the correlation with the physical properties that the present invention aims to achieve, it has been confirmed that the physical properties are not affected.

[0033] In the spatial distribution of the elastic modulus measured as described above, the surface of the resin layer of the present invention is characterized by having an elastic modulus difference between region A and region B. In this case, the region with the higher elastic modulus is called region A, and the region with the lower elastic modulus is called region B.

[0034] Here, an ideal phase structure will be described with reference to the drawings. The shapes formed by two different types of regions are roughly divided into a so-called "sea-island structure (FIG. 5)" in which one domain is enclosed in the other domain, and a "lamella structure (FIG. 6)" that does not have a closed region within the measurement field of view. It is preferable that the elastic modulus distribution on the surface of the resin layer of the present invention is a sea-island structure, and the island side is a region B31 with a low elastic modulus. In a state in which region B forms a continuous phase structure, the size of region B is too large, so that the physical properties of region A32 and region B appear separately during peeling, and the peeling force becomes unstable. The specific analysis procedure for region A and region B, and the judgment criteria when two regions do not exist will be described later in the Examples section. Note that when three or more regions with different elastic moduli are formed by combining the preferred resin layer coating composition described later, the region with the highest elastic modulus is designated as A and the other regions are designated as B, and the average elastic modulus and total number of them satisfy the above-mentioned conditions, and it is possible to obtain the same effect.

[0035] The reason why the problem of the present invention, that is, the quality of the resin layer is less likely to be degraded and the peeling force can be reduced by providing the above-mentioned structure on the surface of the resin layer, is as follows: The peeling force when peeling between the resin layer and the release layer is considered to be composed of 1) an increase in surface free energy corresponding to the increased surface area due to the peeling between the resin layer and the release layer, and 2) the energy required for deformation of the peeling interface during peeling.

[0036] In contrast, the method described in Patent Document 1 focuses on the release layer (peeling layer) and uses a polydimethylsiloxane copolymer on the peeling layer side to reduce the increase in surface energy caused by peeling (1), and soften the layer to reduce the energy required for deformation of the peeling interface (2), thereby reducing the peeling force. On the other hand, when applied to a coating composition for hard coat, cissing occurs during application as described above because the surface free energy is reduced in (1), and the problem of the present invention cannot be solved.

[0037] On the other hand, the present invention focuses on the resin layer side, rather than on the release layer approach, which may cause a deterioration in quality during the resin layer formation process, and has found that the peel force can be reduced from the viewpoint of 2) above. Furthermore, the present invention has been used as a method for reducing the deformation energy of the peel interface without impairing the function of the resin layer (for example, bulk physical properties such as scratch resistance in the case of a hard coat layer), which is the purpose of the laminate of the present invention. In the present invention, region A and region B are provided on the surface of the resin layer, and the function of the resin layer is secured in region A, and region B is provided, thereby achieving a reduction in the energy required for deformation of the peel interface.

[0038] In this invention, regions A and B are defined as those observed on the surface of the resin layer of the laminate, but it is presumed that a similar structure is also formed between the resin layer and the release layer, and that this function is expressed.

[0039] Elastic modulus E of region B B It is necessary that the compressive strength is 1,500 MPa or less (condition 1), and it is preferable that the compressive strength is 1,000 MPa or less. B If the compressive strength exceeds 1,500 MPa, the aforementioned effect of reducing the peeling force may not be obtained.

[0040] Furthermore, there is a range that must be satisfied for the average number of regions B present per unit area. Specifically, as in condition 2 described above, the average number of regions B within a 5 μm square visual field must be 50 or more and 300 or less (condition 2). If the number of regions B present within a 5 μm square visual field is less than 50, the effect of reducing the peel force, which is the object of the present invention, may be insufficient. On the other hand, if the number of regions B present within a 5 μm square visual field exceeds 300, the function required of the resin layer may be reduced. Elastic modulus E B The method of measurement and the method of analyzing the number of regions B present within a 5 μm square field of view will be described later in the Examples section.

[0041] [Mode of the present invention] Hereinafter, the embodiment of the present invention will be described in detail.

[0042] [Laminate, resin layer, and resin film] The laminate of the present invention has a release layer and a resin layer on at least one surface of the support substrate in this order from the support substrate side. The resin layer in the present invention refers to a layer formed on the support substrate and capable of being peeled off and transferred from the support substrate. A layer formed on the support substrate but not peelable from the support substrate, such as a release layer described later, is not included in the resin layer. The criteria for determining whether or not the layer can be peeled off are evaluated by the cross-cut method described in JIS K5600-5-6:1999, and those with a classification of 4 or higher are peelable, and those with a classification of 0 to 3 are not peelable. The laminate is a combination of the resin layer, the release layer, and the support substrate. When only one layer is formed on the release layer, the layer is a resin layer, and when two or more layers are formed on the release layer, the two or more layers excluding the release layer are one resin layer. In addition, the resin layer peeled off from the support substrate and the release layer may be described as a "resin film" to clarify that the support substrate and the release layer are not included.

[0043] Here, the layer refers to a portion that can be distinguished from an adjacent portion in the thickness direction from the surface side of the laminate in the thickness direction by having an interface and has a finite thickness. More specifically, it refers to a portion that can be distinguished by the presence or absence of a discontinuous interface when the cross section of the laminate is observed with an electron microscope (transmission type, scanning type) or an optical microscope. Therefore, even if the composition changes in the thickness direction of the resin layer, if there is no interface between them, it is treated as one layer.

[0044] The laminate of the present invention may be in a planar state or a three-dimensional shape as long as it has a resin layer exhibiting the above-mentioned physical properties. The thickness of the entire resin layer is preferably 0.5 μm or more and 20 μm or less, more preferably 1 μm or more and 15 μm or less.

[0045] The resin layer may have other functions such as gloss, fingerprint resistance, moldability, designability, scratch resistance, antifouling, solvent resistance, antireflection, antistatic, electrical conductivity, heat ray reflection, near infrared absorption, electromagnetic wave shielding, and easy adhesion.

[0046] Furthermore, one or more layers may be formed on the resin layer. For example, a functional layer having the above-mentioned functions, an adhesive layer, an electronic circuit layer, a printing layer, an optical adjustment layer, or other functional layers may be provided.

[0047] The resin film of the present invention can be obtained, for example, by peeling off the support substrate including the release layer from the aforementioned laminate.

[0048] [Elastic modulus E of region A of the resin layer A and the elastic modulus E of region B B Difference with The conditions for the elastic modulus distribution that the resin layer and resin film of the present invention should satisfy have been described above, but there are other preferable conditions for achieving the objective. Specifically, the elastic modulus E A and the elastic modulus E of region B B There is a preferable range of difference between A -E B The difference in elastic modulus between the two regions is a more preferable parameter for ensuring the functionality of the resin layer and the resin film in the region A and reducing the energy required for deformation of the peeling interface in the region B. The difference in elastic modulus (E A -E B If the modulus of elasticity E is less than 100 MPa, the effect of reducing the peeling force may be insufficient. A and the elastic modulus E B Although there is no particular problem if the difference is large, the limit for the materials that can be used in reality is about 20,000 MPa. The specific measurement and analysis methods for the elastic modulus of each region will be described later in the Examples section.

[0049] [Major axis radius of region B of resin layer and resin film] Furthermore, there is a preferred form for the shape of the region B having a relatively low elastic modulus formed on the surface of the laminate and resin film of the present invention. Specifically, it is preferable that the major axis radius of the region B is 25 nm or more and 250 nm or less. Here, the major axis radius means the radius of the major axis side of the ellipse obtained by elliptical approximation of the shape formed by the region B on the surface of the resin layer and the resin film. In order for the region B to contribute to macroscopic physical properties such as peeling force and handling property, it is necessary to have a certain size or more, and the correlation can be evaluated by using the major axis of the elliptical approximation. If the major axis radius exceeds 250 nm, the function required for the resin layer and the resin film described above may be reduced, and if it is less than 25 nm, the effect of reducing the peeling force described above may not be obtained. The specific measurement and analysis method of the major axis radius of the region B will be described later in the Examples section.

[0050] [Surface composition of resin layer and resin film] Furthermore, preferred components exist in the surface composition of the resin layer and the resin film, more specifically, in each of the regions A and B. Specifically, within a depth range of 5 nm from the surface of the resin layer and the resin film, region A preferably contains a resin component represented by Chemical Formula 1, and region B preferably contains a resin component represented by Chemical Formula 2 and / or Chemical Formula 3. In this case, region B may contain the resin component represented by Chemical Formula 1, but it is particularly preferred that region A does not contain, or contains relatively little, the resin component represented by Chemical Formula 2 and / or Chemical Formula 3.

[0051] [ka]

[0052] [ka]

[0053] [ka]

[0054] R1 is hydrogen or a methyl group, R 2 , R 3 , R 4 is one of the following (i) to (vi). (i) a substituted or unsubstituted alkylene group (ii) a substituted or unsubstituted arylene group (iii) a substituted alkylene group having an ether group, an ester group, or an amide group therein (iv) an unsubstituted alkylene group having an ether group, an ester group, or an amide group therein (v) a substituted arylene group having an ether group, an ester group, or an amide group therein (vi) An unsubstituted arylene group having an ether group, an ester group or an amide group therein.

[0055] Here, the surface composition of the resin layer and the resin film is a more preferable parameter for ensuring the functionality of the resin layer and the resin film by the above-mentioned region A and reducing the energy required for deformation of the peeling interface by region B. In order for the material constituting region B to effectively affect the peeling force, it is preferable that it is present in the vicinity of the surface of the resin layer and the resin film, specifically, within a range of 5 nm from the surface in the depth direction.

[0056] The evaluation and analysis methods for the resin components containing the above chemical formulas will be described later in the Examples section, but for example, analysis can be performed by using a time-of-flight-secondary ion mass spectrometry (TOF-SIMS) in combination with ion sputtering. While performing sputtering to a depth of 5 nm from the surface by ion sputtering, TOF-SIMS measurements are performed, and analysis is performed based on the integrated values.

[0057] The resin component represented by Chemical Formula 1 can be detected using the negative ions with mass number 85 (Chemical Formula 4) or the negative ions with mass number 71 (Chemical Formula 5). In other words, if either the negative ions with mass number 85 (Chemical Formula 4) or the negative ions with mass number 71 (Chemical Formula 5) are detected, it means that the resin component represented by Chemical Formula 1 is present.

[0058] [ka]

[0059] [ka]

[0060] On the other hand, the resin component represented by chemical formula 2 can be detected using a positive ion with a mass number of 69 (chemical formula 6) and a positive ion with a mass number of 169 (chemical formula 7). When these positive ions are detected simultaneously, it can be determined that chemical formula 2 is present.

[0061] [ka]

[0062] [ka]

[0063] In addition, the resin component represented by chemical formula 3 is a positive ion with a mass number of 45 (C2H5O + ) and the positive ion with mass number 59 (C3H7O + ) can be used to detect the positive ion with mass number 45 (C2H5O + If either the mass number 59 or the mass number 59 is detected, it means that the resin component represented by chemical formula 3 is present.

[0064] Furthermore, when determining whether each of the above components is contained in each region, TOF-SIMS mapping is performed. Ions characteristic of each compound are mapped, and verification is performed by comparing the shape of the region obtained from the elastic modulus distribution. The relative content can also be estimated from the strength of the signal intensity during mapping. The specific measurement procedure will be described later.

[0065] [Supporting base material] The resin constituting the support substrate used in the laminate of the present invention may be either a thermoplastic resin or a thermosetting resin, and may be a homogeneous resin, a copolymer, or a blend of two or more kinds. The resin constituting the support substrate is preferably one having good moldability, and from that point of view, a thermoplastic resin is more preferable.

[0066] Examples of the thermoplastic resin include polyolefin resins such as polyethylene, polypropylene, polystyrene, and polymethylpentene, alicyclic polyolefin resins, polyamide resins such as nylon 6 and nylon 66, aramid resins, polyimide resins, polyester resins, polycarbonate resins, polyarylate resins, polyacetal resins, polyphenylene sulfide resins, fluororesins such as tetrafluoroethylene resin, trifluoroethylene resin, trifluorochloroethylene resin, tetrafluoroethylene-hexafluoropropylene copolymer, and vinylidene fluoride resin, acrylic resins, methacrylic resins, polyacetal resins, polyglycolic acid resins, and polylactic acid resins. Examples of the thermosetting resins include phenolic resins, epoxy resins, urea resins, melamine resins, unsaturated polyester resins, polyurethane resins, polyimide resins, and silicone resins. The thermoplastic resin is preferably a resin having sufficient stretchability and conformability. From the viewpoint of strength and heat resistance, the thermoplastic resin is more preferably a polyester resin, a polycarbonate resin, an acrylic resin, or a methacrylic resin.

[0067] The polyester resin in the present invention is a general term for a polymer having an ester bond as the main bond in the main chain, and is obtained by polycondensation of an acid component and its ester with a diol component. Specific examples include polyethylene terephthalate, polypropylene terephthalate, polyethylene-2,6-naphthalate, and polybutylene terephthalate. These may also be copolymerized with other dicarboxylic acids and their esters or diol components as the acid component or diol component. Among these, polyethylene terephthalate and polyethylene-2,6-naphthalate are particularly preferred in terms of transparency, dimensional stability, heat resistance, and the like.

[0068] On the other hand, for the purpose of inspecting the optical properties in the laminate manufacturing process, the transparent support is preferably a transparent material with low birefringence, and from the viewpoint of low birefringence, cellulose ester and cyclic olefin are preferable. Commercially available norbornene-based polymers that can be used include Arton (manufactured by JSR Corporation), Zeonex, Zeonor (all manufactured by Zeon Corporation), TOPAS (manufactured by Polyplastics Corporation), etc.

[0069] The support substrate may contain various additives, such as an antioxidant, an antistatic agent, a crystal nucleating agent, inorganic particles, organic particles, a viscosity reducer, a heat stabilizer, a lubricant, an infrared absorbing agent, an ultraviolet absorbing agent, a dopant for adjusting the refractive index, etc. The support substrate may have either a single layer structure or a laminate structure.

[0070] Before forming the resin layer, various surface treatments can be performed. Examples of surface treatments include chemical treatment, mechanical treatment, corona discharge treatment, flame treatment, ultraviolet irradiation treatment, high frequency treatment, glow discharge treatment, active plasma treatment, laser treatment, mixed acid treatment, and ozone oxidation treatment. Among these, glow discharge treatment, ultraviolet irradiation treatment, corona discharge treatment, and flame treatment are preferred, and glow discharge treatment and ultraviolet treatment are more preferred. In addition, the surface of the support substrate can be provided in advance with a plurality of functional layers such as an easy-adhesion layer, an antistatic layer, an undercoat layer, and an ultraviolet absorbing layer.

[0071] The supporting substrate is not particularly limited as long as the resin layer can be transferred onto it, but it is preferable to use a supporting substrate having a release layer on the surface in contact with the resin layer. The release layer will be described in detail later.

[0072] [Release layer and method of manufacturing the release layer] The above-mentioned supporting substrate preferably has a release layer satisfying the above-mentioned conditions on at least one surface in contact with the resin layer. The supporting substrate side of the release layer may be composed of a plurality of layers from the viewpoint of imparting adhesion, antistatic property, solvent resistance, etc.

[0073] The thickness of the release layer is not particularly limited, but is preferably 10 to 500 nm, more preferably 20 to 200 nm, from the standpoint of the in-plane uniformity, quality, and peeling force of the release layer.

[0074] The material for the release layer is not particularly limited, but it is preferably formed from a resin composition for the release layer described below, and it is preferably formed on the surface of the supporting substrate by coating, drying, and curing using the method for producing a release layer described below.

[0075] The material of the resin composition for the release layer is not particularly limited as long as the surface in contact with the resin layer has the standard deviation and average value of the specific elastic modulus distribution described above. However, preferred materials include alkyd-based resins, polyolefin-based resins, resins containing long-chain alkyl groups, fluorine-based resins, silicone-based resins, and mixed or copolymer resins of organic and silicone resins.

[0076] The method for producing the release layer is not particularly limited as long as the surface in contact with the resin layer has the specific standard deviation and average value of the elastic modulus distribution described above. However, it is preferable to form a coating layer by applying a coating composition for the release layer by a dip coating method, roller coating method, wire bar coating method, gravure coating method or die coating method (U.S. Pat. No. 2,681,294 specification), etc., and gravure coating method or die coating method is preferred.

[0077] Next, the coating layer applied onto the supporting substrate or the like is dried. In order to completely remove the solvent from the resulting coating layer, and also from the viewpoint of promoting the curing of the coating film, it is preferable that the drying step be accompanied by heating of the coating film.

[0078] Drying methods include heat transfer drying (contact with a hot object), convection heat transfer (hot air), radiation heat transfer (infrared rays), and others (microwaves, induction heating), etc. Among these, in the manufacturing method of the present invention, a method using convection heat transfer or radiation heat transfer is preferred because it is necessary to precisely make the drying speed uniform even in the width direction.

[0079] Furthermore, a further curing operation (curing step) may be performed by irradiating heat or energy rays. In the curing step, when curing is performed by heat, the temperature is preferably from room temperature to 200° C., and from the viewpoint of activation energy of the curing reaction, the temperature is more preferably 100° C. or higher and 200° C. or lower, and further preferably 130° C. or higher and 200° C. or lower.

[0080] When curing is performed using energy rays, electron beams (EB rays) and / or ultraviolet rays (UV rays) are preferred from the viewpoint of versatility. Examples of the type of ultraviolet lamp used for irradiating ultraviolet rays include discharge lamp type, flash type, laser type, and electrodeless lamp type. When curing with ultraviolet rays using a high-pressure mercury lamp of the discharge lamp type, the illuminance of the ultraviolet rays is preferably 100 to 3,000 (mW / cm2). 2 ), more preferably 200 to 2,000 (mW / cm 2 ), and more preferably 300 to 1,500 (mW / cm 2 ), and the integrated light quantity of the ultraviolet light is preferably 100 to 3,000 (mJ / cm 2 ), more preferably 200 to 2,000 (mJ / cm 2 ), and more preferably 300 to 1,500 (mJ / cm 2) where UV illuminance is the radiation intensity received per unit area, and varies with lamp output, emission spectral efficiency, diameter of the light-emitting bulb, design of the reflector, and the distance between the irradiated object and the light source. However, illuminance does not vary with transport speed. Additionally, the integrated UV light quantity is the radiation energy received per unit area, and is the total amount of photons that reach the surface. The integrated light quantity is inversely proportional to the radiation speed passing under the light source, and proportional to the number of irradiations and the number of lamps.

[0081] As described above, it is preferable to form a release layer on the supporting substrate by drying and curing the coating layer formed on the supporting substrate.

[0082] [Method of manufacturing laminate] The method for producing the laminate of the present invention is preferably a method for producing a laminate in which a preferred resin layer coating composition described below is applied onto the release layer of the preferred support substrate, and then dried and cured to form a resin layer. The coating method is not particularly limited, and can be appropriately selected from dip coating, roller coating, wire bar coating, gravure coating, die coating (U.S. Pat. No. 2,681,294), and the like.

[0083] Here, it is important that the surface properties of the resin layer satisfy the above-mentioned conditions, and the manufacturing method may be capable of forming a resin layer having a different resin composition in the thickness direction. When forming a resin layer having a different resin composition in the thickness direction, the manufacturing method of the laminate is preferably a method of successively or simultaneously applying at least two or more kinds of coating compositions for the resin layer, followed by drying and curing to form a resin layer, and more preferably a manufacturing method of the laminate in which at least two or more kinds of coating compositions for the resin layer are simultaneously applied.

[0084] In the drying step, the coating film applied onto a supporting substrate etc. is dried. In addition to completely removing the solvent from the resulting laminate, it is preferable that the drying step be accompanied by heating the coating film.

[0085] Heating methods in the drying process include heat transfer drying (contact with a hot object), convection heat transfer (hot air), radiation heat transfer (infrared rays), and others (microwaves, induction heating), etc. Among these, methods using convection heat transfer or radiation heat transfer are preferred because of the need to precisely uniform the drying speed in the width direction.

[0086] The drying step may be followed by a further curing operation (curing step) by irradiation with heat or active energy rays.

[0087] As the active energy ray, from the viewpoint of versatility, an electron beam (EB ray) and / or an ultraviolet ray (UV ray) are preferable. When curing with ultraviolet ray, it is preferable that the oxygen concentration is as low as possible in order to prevent oxygen inhibition, and it is more preferable to cure in a nitrogen atmosphere (nitrogen purging). When the oxygen concentration is high, the curing of the outermost surface is inhibited, the curing of the surface is weakened, and the toughness may be reduced. In addition, examples of the type of ultraviolet lamp used for irradiating ultraviolet ray include a discharge lamp type, a flash type, a laser type, and an electrodeless lamp type. When a high-pressure mercury lamp, which is a discharge lamp type, is used, the illuminance of the ultraviolet ray is preferably 100 to 3,000 mW / cm. 2 , more preferably 200 to 2,000 mW / cm 2 , and more preferably 300 to 1,500 mW / cm 2 The ultraviolet irradiation is preferably performed under the conditions described above. The integrated light amount of the ultraviolet light is preferably 100 to 3,000 mJ / cm 2 , more preferably 200 to 2,000 mJ / cm 2 , and more preferably 300 to 1,500 mJ / cm 2 It is best to irradiate ultraviolet light under the following conditions: Here, ultraviolet light illuminance refers to the irradiation strength received per unit area, and varies with lamp output, emission spectral efficiency, diameter of the light-emitting bulb, design of the reflector, and the distance between the irradiated object and the light source. However, illuminance does not vary with transport speed. Also, the integrated amount of ultraviolet light refers to the irradiation energy received per unit area, and is the total amount of photons that reach the surface. The integrated amount of light is inversely proportional to the irradiation speed passing under the light source, and proportional to the number of irradiations and the number of lamps.

[0088] [Coating composition for resin layer] The method for producing the laminate of the present invention is not particularly limited, but the laminate of the present invention can be obtained by applying a coating composition for the resin layer onto the release layer of the above-mentioned supporting substrate, and drying and curing the composition as necessary.

[0089] Here, the term "resin layer coating composition" refers to a liquid consisting of a solvent and a solute, which can be applied to the aforementioned support substrate, volatilized and removed in the process of drying the solvent, and further cured as necessary to form a resin layer. Here, the "type" of resin layer coating composition refers to a liquid in which the type of solute constituting the resin layer coating composition is different even in part. The solute consists of a resin or a material capable of forming the resin or a solute in the coating process (hereinafter referred to as a resin precursor), particles, and various additives such as a polymerization initiator, a curing agent, a catalyst, a leveling agent, an ultraviolet absorber, and an antioxidant.

[0090] [Resin precursor] The resin precursor can be used by itself or by dissolving it in a solvent to prepare a coating composition for a resin layer. In particular, it is preferable to use a resin precursor as a material for forming region A. The resin precursor refers to a material that can harden a coating film by volatilization of a solvent and polymerization and crosslinking reaction of itself. That is, the resin layer of the laminate of the present invention and the resin film obtained by peeling off the release film from the laminate contain a cured product obtained by crosslinking the resin precursor.

[0091] In the above-mentioned method for producing the laminate of the present invention, the resin precursor is preferably a material that can be polymerized by active energy rays, either by itself or in combination with a photopolymerization initiator that can be cleaved by active energy rays, to harden the coating film.

[0092] Specifically, preferred resin precursors when ultraviolet light is used as the active energy ray and a photopolymerization initiator is used in combination are polyfunctional (meth)acrylate monomers, (meth)acrylate oligomers, alkoxysilanes having a (meth)acrylic group, alkoxysilane hydrolysates having a (meth)acrylic group, alkoxysilane oligomers having a (meth)acrylic group, acrylic polymers having a (meth)acrylic group, urethane polymers having a (meth)acrylic group, epoxy polymers having a (meth)acrylic group, and silicone polymers having a (meth)acrylic group.

[0093] Examples of polyfunctional acrylate monomers include polyfunctional acrylates having two or more (meth)acryloyloxy groups in one molecule and modified polymers thereof, and specific examples thereof include pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol tri(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol triacrylate hexanemethylene diisocyanate urethane polymer, etc. These monomers can be used alone or in combination of two or more.

[0094] In addition, commercially available polyfunctional acrylic compositions include Mitsubishi Rayon Co., Ltd. (product name "Diabeam" (registered trademark) series, etc.), Nagase & Co., Ltd. (product name "Denacol" (registered trademark) series, etc.), Shin-Nakamura Chemical Co., Ltd. (product name "NK Ester" series, etc.), DIC Corporation (product name "UNIDIC" (registered trademark), etc.), Toagosei Co., Ltd. ("Aronix" (registered trademark) series, etc.), NOF Corporation ("Blenmar" (registered trademark) series, etc.), Nippon Kayaku Co., Ltd. (product name "KAYARAD" (registered trademark) series, etc.), Kyoeisha Chemical Co., Ltd. (product name "Light Ester" series, etc.), and these products can be used.

[0095] The acrylic polymer having a (meth)acrylic group is preferably synthesized by a polymerization reaction of a multifunctional acrylate monomer (e.g., polyol acrylate, polyester acrylate, urethane acrylate, epoxy acrylate). Examples of the urethane polymer include melamine polyurethane. As the silicone polymer, a cohydrolyzate of a silane compound (e.g., tetraalkoxysilane, alkyltrialkoxysilane) and a silane coupling agent having a reactive group (e.g., epoxy, methacryl) is preferably used. In addition, various polymers that do not contain an unsaturated group, have a weight average molecular weight of 5,000 to 200,000, and have a glass transition temperature of 20 to 200°C can be used.

[0096] The resin layer and resin film of the laminate of the present invention preferably contain a cured product obtained by curing two types of resin precursors, and more preferably, the combination of the resin precursors is within a specific range. Specifically, of the two types of resin precursors, it is preferable that the resin precursor having a smaller functional group equivalent (referred to as resin precursor A) and the resin precursor having a larger functional group equivalent (referred to as resin precursor B) satisfy the following conditions.

[0097] The functional group equivalent (QA) of the resin precursor A and the functional group equivalent (QB) of the resin precursor B satisfy the following formula.

[0098] 0.01< QA / QB <0.05 100(g / eq)< QA < 400(g / eq) The term "functional group equivalent" as used herein refers to the value obtained by dividing the weight-average molecular weight of the resin precursor by the number of functional groups, which are capable of causing a crosslinking reaction.

[0099] When the two types of resin precursors satisfy the above-mentioned conditions, the crack resistance of the resin layer or resin film is improved.

[0100] Furthermore, Resin Precursor A and Resin Precursor B preferably contain segments of Chemical Formula 8 and Chemical Formula 9. By containing the segments of Chemical Formula 8 and 9, interaction between the respective segments can be brought about, and thus toughness can be imparted.

[0101] [ka]

[0102] [ka]

[0103] Here, R6 is hydrogen or a methyl group, and R5 is any one of the following (i) to (vi). (i) a substituted or unsubstituted alkylene group (ii) a substituted or unsubstituted arylene group (iii) a substituted alkylene group having an ether group, an ester group, or an amide group therein (iv) an unsubstituted alkylene group having an ether group, an ester group, or an amide group therein (v) a substituted arylene group having an ether group, an ester group, or an amide group therein (vi) an unsubstituted arylene group having an ether group, an ester group or an amide group therein [Leveling agent] A preferred resin layer coating composition used to form the resin layer of the present invention preferably contains a leveling agent. It is particularly preferred to configure region B with a leveling agent, which allows the peeling force to be designed within a suitable range while maintaining the function of the resin layer. Examples of leveling agents include acrylic copolymers, silicone-based, and fluorine-based leveling agents. Among these, particularly preferred leveling agents are those containing a hexafluoropropylene group or a polyether group. If the leveling agent contains the above functional group, the coating quality and peeling force can be suitably designed.

[0104] [Particle material, particle component] The resin layer of the laminate of the present invention may contain a particle component. Here, the particles may be either inorganic particles or organic particles, but inorganic particles are preferred from the viewpoint of scratch resistance.

[0105] The number of types of inorganic particles is preferably 1 to 20. The number of types of inorganic particles is more preferably 1 to 10, and particularly preferably 1 to 4. Here, "inorganic particles" also includes those that have been subjected to a surface treatment. This surface treatment refers to the introduction of a compound to the particle surface by chemical bonding (including covalent bonding, hydrogen bonding, ionic bonding, van der Waals bonding, hydrophobic bonding, etc.) or adsorption (including physical adsorption and chemical adsorption).

[0106] Here, the type of inorganic particles is determined by the type of elements that make up the inorganic particles, and in the case of performing some surface treatment, it is determined by the type of elements that make up the particles before the surface treatment. For example, titanium oxide (TiO2) and nitrogen-doped titanium oxide (TiO2), in which part of the oxygen in titanium oxide is replaced with nitrogen, an anion, are 2-x N x ) are different types of inorganic particles because the elements that make up the inorganic particles are different. Also, if there are multiple particles (ZnO) consisting of the same elements, such as Zn and O, even if there are multiple particles with different number average particle sizes or different composition ratios of Zn and O, these are the same type of particles. Also, even if there are multiple Zn particles with different oxidation numbers, as long as the elements that make up the particles are the same (in this example, as long as all elements other than Zn are the same), these are the same type of particles.

[0107] Here, the particles present in the resin layer coating composition used in the present invention are referred to as "particle material", and the particles present in the resin layer formed by applying the resin layer coating composition, drying, curing treatment or vapor deposition or other treatment are referred to as "particle components".

[0108] The inorganic particles are not particularly limited, but are preferably oxides, nitrides, borides, chlorides, carbonates, or sulfates of metals or metalloids. They may be composite oxides containing two types of metals or metalloids, or may have a different element introduced between the lattice, a different element substituted at the lattice points, or lattice defects introduced.

[0109] It is more preferable that the inorganic particles are oxide particles in which at least one metal or semi-metal selected from the group consisting of Si, Al, Ca, Zn, Ga, Mg, Zr, Ti, In, Sb, Sn, Ba and Ce is oxidized.

[0110] Specifically, the material is at least one metal oxide or semi-metal oxide selected from the group consisting of silica (SiO2), aluminum oxide (Al2O3), zinc oxide (ZnO), zirconium oxide (ZrO2), titanium oxide (TiO2), indium oxide (In2O3), tin oxide (SnO2), antimony oxide (Sb2O3) and indium tin oxide (In2O3).

[0111] [solvent] The resin layer coating composition used in the method for producing the laminate of the present invention may contain a solvent, and it is preferable to contain a solvent in order to form a coating film uniformly in the plane and to gradually change the composition within one layer. The number of types of solvents is preferably 1 to 20, more preferably 1 to 10, even more preferably 1 to 6, and particularly preferably 1 to 4.

[0112] The term "solvent" as used herein refers to a substance that is liquid at room temperature and pressure and can be evaporated almost entirely in the drying process after application.

[0113] Here, the type of solvent is determined by the molecular structure that constitutes the solvent. In other words, solvents that have the same elemental composition and the same type and number of functional groups but different bond relationships (structural isomers), and solvents that are not structural isomers but do not overlap exactly in any conformation in three-dimensional space (stereoisomers) are treated as different types of solvents. For example, 2-propanol and n-propanol are treated as different solvents.

[0114] [Other components in the resin layer coating composition] In addition, the coating composition for the resin layer preferably contains a polymerization initiator, a curing agent, and a catalyst. The polymerization initiator and the catalyst are used to promote the curing of the resin layer. As the polymerization initiator, one that can initiate or promote the polymerization, condensation, or crosslinking reaction of the components contained in the coating composition for the resin layer by anionic, cationic, or radical polymerization reaction or the like is preferable.

[0115] Various polymerization initiators, curing agents, and catalysts can be used. The polymerization initiators, curing agents, and catalysts may be used alone, or multiple polymerization initiators, curing agents, and catalysts may be used simultaneously. Furthermore, an acid catalyst or a thermal polymerization initiator may be used in combination. Examples of acid catalysts include hydrochloric acid aqueous solution, formic acid, and acetic acid. Examples of thermal polymerization initiators include peroxides and azo compounds. Examples of photopolymerization initiators include alkylphenone compounds, sulfur-containing compounds, acylphosphine oxide compounds, and amine compounds. Examples of crosslinking catalysts that promote the reaction of forming urethane bonds include dibutyltin dilaurate and dibutyltin diethylhexoate.

[0116] The resin layer coating composition may also contain other crosslinking agents, such as melamine crosslinking agents, such as alkoxymethylol melamine, acid anhydride crosslinking agents, such as 3-methyl-hexahydrophthalic anhydride, and amine crosslinking agents, such as diethylaminopropylamine.

[0117] As the photopolymerization initiator, an alkylphenone compound is preferable from the viewpoint of curability. Specific examples of the alkylphenone compound include 1-hydroxy-cyclohexyl-phenyl-ketone, 2,2-dimethoxy-1,2-diphenylethane-1-one, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-phenyl)-1-butane, 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-(4-phenyl)-1-butane, 2-benzyl-2-dimethylamino-1-(4- morpholinophenyl)-1-butane, 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butane, 1-cyclohexyl-phenyl ketone, 2-methyl-1-phenylpropan-1-one, 1-[4-(2-ethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, bis(2-phenyl-2-oxoacetate)oxybisethylene, and polymerized versions of these materials.

[0118] As long as the effect of the present invention is not hindered, an ultraviolet absorber, a lubricant, an antistatic agent, etc. may be added to the resin layer coating composition used to form the resin layer. This allows the resin layer to contain an ultraviolet absorber, a lubricant, an antistatic agent, etc. Specific examples of ultraviolet absorbers include benzophenone-based, benzotriazole-based, oxalic acid anilide-based, triazine-based, and hindered amine-based ultraviolet absorbers. Examples of antistatic agents include metal salts such as lithium salts, sodium salts, potassium salts, rubidium salts, cesium salts, magnesium salts, and calcium salts.

[0119] As described above, it is preferable to form the resin layer by drying and curing the coating layer formed on the release layer.

[0120] [Application] The laminate of the present invention can be suitably used for protecting the surface of a molded product made of, for example, plastics or metal, taking advantage of its scratch resistance, conformability to surface shape, etc. Furthermore, a resin film obtained by peeling off the support substrate and the release layer from the laminate of the present invention can be suitably used, for example, as a protective film for a molded product.

[0121] [Resin film] As mentioned above, a resin layer that does not have a supporting substrate and a release layer is referred to as a resin film. The resin film of the present invention is characterized in that, when observed with an atomic force microscope, there is a region on the surface having a lower elastic modulus (referred to as region B) than a region having a higher elastic modulus (referred to as region A), and that it satisfies the following conditions 1 and 2. Condition 1: Elastic modulus E of region B B is 1,500MPa or less Condition 2: The average number of regions B in a 5 μm square is 50 to 300. Details of region A, region B, condition 1, and condition 2 are as described above in the section on the resin layer of the laminate of the present invention.

[0122] In addition, the resin film of the present invention preferably satisfies the following conditions 3 and 4. Condition 3: Elastic modulus E of the region A A and the elastic modulus E of the region B B The difference between A -E B ) is 100MPa or more. Condition 4: The major axis radius of the region B is 25 nm or more and 250 nm or less. Details of Condition 3 and Condition 4 are as described above in the section on the resin layer of the laminate of the present invention.

[0123] Furthermore, in the resin film of the present invention, it is preferable that, within a range of 5 nm from the surface, the region A contains a resin component represented by Chemical Formula 1, and the region B contains a resin component represented by Chemical Formula 2 and / or a resin component represented by Chemical Formula 3. Details of the resin components represented by Chemical Formulas 1, 2, and 3 are as described above in the section on the resin layer of the laminate of the present invention.

[0124] The method for producing the resin film of the present invention is not particularly limited. For example, the resin film of the present invention can be produced by producing the laminate of the present invention and then peeling off only the resin layer from the laminate.

[0125] As described above, the resin film of the present invention can be suitably used, for example, as a protective film for a molded article. EXAMPLES

[0126] Next, the present invention will be described based on examples, but the present invention is not necessarily limited to these.

[0127] [Release layer coating composition 1] The following materials were mixed and diluted with a mixed solvent of methyl ethyl ketone / isopropyl alcohol (mixture ratio by mass: 50 / 50) to obtain coating composition 1 for a release layer having a solid content concentration of 5 mass %. Side-chain carbinol modified reactive silicone oil (X-22-4015 Shin-Etsu Chemical Co., Ltd. Solid content 100% by mass): 5 parts by mass ·Both-end polyether modified reactive silicone oil (X-22-4952 Shin-Etsu Chemical Co., Ltd. Solid content 100% by mass): 5 parts by mass Acrylic modified alkyd resin (Hariftar KV-905, Harima Chemicals Co., Ltd., solid content concentration 53% by mass) 100 parts by mass Isobutyl alcohol modified melamine resin (Melan 2650L Hitachi Chemical Co., Ltd. Solid content concentration 60% by mass): 20 parts by mass · Paratoluenesulfonic acid: 5 parts by weight.

[0128] [Release layer coating composition 2] The following materials were mixed and diluted with a toluene / heptane mixed solvent (mass mixing ratio 50 / 50) to obtain coating composition 3 for a release layer having a solid content concentration of 2 mass %. Methylvinylpolysiloxane and methylhydrogenpolysiloxane in toluene (LTC752 Coating, manufactured by Dow Corning Toray Co., Ltd., solid content concentration 30% by mass): 85 parts by mass Stripping additives (BY24-4980, manufactured by Dow Corning Toray Co., Ltd., solid content concentration 30% by mass): 5 parts by mass ·Methylvinylpolysiloxane and platinum complex solution (PL-50T manufactured by Shin-Etsu Chemical Co., Ltd.): 0.1 parts by mass.

[0129] [Release layer coating composition 3] The following materials were mixed and diluted with a mixed solvent of methyl ethyl ketone / isopropyl alcohol (mixture ratio by mass: 50 / 50) to obtain coating composition 5 for a release layer having a solids concentration of 5% by mass. ·Toluene / xylene / isobutanol / methanol mixed solution of aminoalkyd resin containing long chain alkyl groups (Tesfine, manufactured by Hitachi Chemical Co., Ltd.) R 305, solid content concentration 50% by mass).

[0130] [Release layer coating composition 4] The following materials were mixed and diluted with a mixed solvent of methyl ethyl ketone / isopropyl alcohol (mixture ratio by mass: 50 / 50) to obtain coating composition 5 for a release layer having a solids concentration of 5% by mass. ·One-end carbinol modified reactive silicone oil (X-22-170DX Shin-Etsu Chemical Co., Ltd. Solid content 100% by mass): 1 part by mass ·Both-end polyether modified reactive silicone oil (X-22-4952 Shin-Etsu Chemical Co., Ltd. Solid content 100% by mass): 5 parts by mass Acrylic modified alkyd resin (Hariftar KV-905, Harima Chemicals Co., Ltd., solid content concentration 53% by mass) 100 parts by mass Isobutyl alcohol modified melamine resin (Melan 2650L Hitachi Chemical Co., Ltd. Solid content concentration 60% by mass): 20 parts by mass · Paratoluenesulfonic acid: 5 parts by weight.

[0131] [Preparation of coating composition for resin layer] [Coating composition 1 for resin layer] The following materials were mixed and diluted with methyl ethyl ketone to obtain a resin layer coating composition 1 having a solids concentration of 20 mass %. Resin precursor A: 160 parts by weight of butyl acetate / ethyl acetate solution of polymer acrylate resin “Unidic” V-6850 DIC Corporation Solid content: 50% by mass Resin precursor B: Urethane acrylate oligomer (“Shiko” UV3200B manufactured by Nippon Gosei Kagaku Kogyo Co., Ltd. Solid content concentration 100% by mass) 20 parts by mass Leveling agent “Futergent” 212M (manufactured by Neos Co., Ltd.) Solid content concentration 100% by mass 1 part by mass α-Hydroxyacetophenone type photopolymerization initiator 3.0 parts by mass (“Irgacure” (registered trademark) 184 manufactured by BASF Japan Ltd.).

[0132] [Coating composition 2 for resin layer] The following materials were mixed and diluted with methyl ethyl ketone to obtain a resin layer coating composition 2 having a solids concentration of 20 mass %. Resin precursor A: 190 parts by weight of butyl acetate / ethyl acetate solution of polymer acrylate resin “Unidic” V-6850 DIC Corporation Solid content: 50% by mass Resin precursor B: Urethane acrylate oligomer (“Shiko” UV3200B manufactured by Nippon Gosei Kagaku Kogyo Co., Ltd. Solid content concentration 100% by mass) 5 parts by mass Leveling agent “Futergent” 602A (manufactured by Neos Co., Ltd., solid content concentration 50% by mass) 1 part by mass α-Hydroxyacetophenone type photopolymerization initiator 3.0 parts by mass (“Irgacure” (registered trademark) 184 manufactured by BASF Japan Ltd.).

[0133] [Coating composition 3 for resin layer] The following materials were mixed and diluted with methyl ethyl ketone to obtain a resin layer coating composition 3 having a solids concentration of 20 mass %. Resin precursor A: 160 parts by weight of butyl acetate / ethyl acetate solution of polymer acrylate resin “Unidic” V-6850 DIC Corporation Solid content: 50% by mass Resin precursor B: Urethane acrylate oligomer (“Shiko” UV3200B manufactured by Nippon Gosei Kagaku Kogyo Co., Ltd. Solid content concentration 100% by mass) 20 parts by mass Leveling agent “BYK” (registered trademark)-UV3535, manufactured by BYK Japan Co., Ltd., solid content concentration 100% by mass, 1 part by mass α-Hydroxyacetophenone type photopolymerization initiator 3.0 parts by mass (“Irgacure” (registered trademark) 184 manufactured by BASF Japan Ltd.).

[0134] [Coating composition for resin layer 4] The following materials were mixed and diluted with methyl ethyl ketone to obtain a resin layer coating composition 4 having a solids concentration of 20 mass %. Resin precursor A: 160 parts by weight of butyl acetate / ethyl acetate solution of polymer acrylate resin “Unidic” V-6850 DIC Corporation Solid content: 50% by mass Resin precursor B: Urethane acrylate oligomer (“Shiko” UV3200B manufactured by Nippon Gosei Kagaku Kogyo Co., Ltd. Solid content concentration 100% by mass) 20 parts by mass Leveling agent “Futergent” 212M Neos Co., Ltd. Solid content concentration 100% by mass 3 parts by mass α-Hydroxyacetophenone type photopolymerization initiator 3.0 parts by mass (“Irgacure” (registered trademark) 184 manufactured by BASF Japan Ltd.).

[0135] [Coating composition for resin layer 5] The following materials were mixed and diluted with methyl ethyl ketone to obtain a resin layer coating composition 5 having a solids concentration of 20 mass %. Resin precursor A: 160 parts by weight of butyl acetate / ethyl acetate solution of polymer acrylate resin “Unidic” V-6850 DIC Corporation Solid content: 50% by mass Resin precursor B: Urethane acrylate oligomer (“Shiko” UV3200B manufactured by Nippon Gosei Kagaku Kogyo Co., Ltd. Solid content concentration 100% by mass) 20 parts by mass Leveling agent “Futergent” 212M (manufactured by Neos Co., Ltd., solid content concentration 100% by mass) 0.3 parts by mass α-Hydroxyacetophenone type photopolymerization initiator 3.0 parts by mass (“Irgacure” (registered trademark) 184 manufactured by BASF Japan Ltd.).

[0136] [Coating composition for resin layer 6] The following materials were mixed and diluted with methyl ethyl ketone to obtain a resin layer coating composition 6 having a solids concentration of 20 mass %. Resin precursor A: 190 parts by weight of butyl acetate / ethyl acetate solution of polymer acrylate resin “Unidic” V-6850 DIC Corporation Solid content: 50% by mass Resin precursor B: Urethane acrylate oligomer (“Shiko” UV3200B manufactured by Nippon Gosei Kagaku Kogyo Co., Ltd. Solid content concentration 100% by mass) 5 parts by mass Leveling agent (LINC-3A Kyoeisha Chemical Co., Ltd. Solid content concentration 100% by mass) 1 part by mass α-Hydroxyacetophenone type photopolymerization initiator 3.0 parts by mass (“Irgacure” (registered trademark) 184 manufactured by BASF Japan Ltd.).

[0137] [Coating composition for resin layer 7] The following materials were mixed and diluted with methyl ethyl ketone to obtain a resin layer coating composition 7 having a solids concentration of 20 mass %. Polymer acrylate resin butyl acetate / ethyl acetate solution 200 parts by weight “Unidic” V-6850 DIC Corporation Solid content: 50% by mass Leveling agent “BYK” (registered trademark)-UV3535, manufactured by BYK Japan Co., Ltd., solid content concentration 100% by mass, 1 part by mass α-Hydroxyacetophenone type photopolymerization initiator 3.0 parts by mass (“Irgacure” (registered trademark) 184 manufactured by BASF Japan Ltd.).

[0138] [Coating composition 8 for resin layer] The following materials were mixed and diluted with methyl ethyl ketone to obtain a resin layer coating composition 3 having a solids concentration of 20 mass %. Resin precursor A: 160 parts by weight of butyl acetate / ethyl acetate solution of polymer acrylate resin “Unidic” V-6850 DIC Corporation Solid content: 50% by mass Resin precursor B: Urethane acrylate oligomer (“Shiko” UV3200B manufactured by Nippon Gosei Kagaku Kogyo Co., Ltd. Solid content concentration 100% by mass) 20 parts by mass Leveling agent “BYK” (registered trademark)-UV3535, manufactured by BYK Japan Co., Ltd., solid content concentration 100% by mass, 3 parts by mass α-Hydroxyacetophenone type photopolymerization initiator 3.0 parts by mass (“Irgacure” (registered trademark) 184 manufactured by BASF Japan Ltd.).

[0139] [Coating composition for resin layer 9] The following materials were mixed and diluted with methyl ethyl ketone to obtain a resin layer coating composition 9 having a solids concentration of 20 mass %. Resin precursor A: 160 parts by weight of butyl acetate / ethyl acetate solution of polymer acrylate resin “Unidic” V-6850 DIC Corporation Solid content: 50% by mass Resin precursor B: Urethane acrylate oligomer (“Shiko” UV3200B manufactured by Nippon Gosei Kagaku Kogyo Co., Ltd. Solid content concentration 100% by mass) 20 parts by mass Leveling agent “BYK” (registered trademark)-UV3535, manufactured by BYK Japan Co., Ltd., solid content concentration 100% by mass, 0.5 parts by mass α-Hydroxyacetophenone type photopolymerization initiator 3.0 parts by mass (“Irgacure” (registered trademark) 184 manufactured by BASF Japan Ltd.).

[0140] [Coating composition 10 for resin layer] The following materials were mixed and diluted with methyl ethyl ketone to obtain a resin layer coating composition 10 having a solids concentration of 20% by mass. Polyfunctional acrylate monomer 100 parts by weight “KAYARAD” (registered trademark) PET30, manufactured by Nippon Kayaku Co., Ltd., solid content concentration 100% by mass α-Hydroxyacetophenone type photopolymerization initiator 3.0 parts by mass (“Irgacure” (registered trademark) 184 manufactured by BASF Japan Ltd.).

[0141] [Coating composition for resin layer 11] The following materials were mixed and diluted with methyl ethyl ketone to obtain a resin layer coating composition 11 having a solids concentration of 20% by mass. Resin precursor A: 160 parts by weight of butyl acetate / ethyl acetate solution of polymer acrylate resin “Unidic” V-6850 DIC Corporation Solid content: 50% by mass “Unidic” V-6850 DIC Corporation Solid content: 50% by mass Resin precursor B: Urethane acrylate oligomer (“Shiko” UV3200B manufactured by Nippon Gosei Kagaku Kogyo Co., Ltd. Solid content concentration 100% by mass) 20 parts by mass Leveling agent “Futergent” 212M (manufactured by Neos Co., Ltd.) Solid content concentration 100% by mass 0.1 parts by mass α-Hydroxyacetophenone type photopolymerization initiator 3.0 parts by mass (“Irgacure” (registered trademark) 184 manufactured by BASF Japan Ltd.).

[0142] [Coating composition 12 for resin layer] The following materials were mixed and diluted with methyl ethyl ketone to obtain a resin layer coating composition 12 having a solids concentration of 20 mass %. Resin precursor A: butyl acetate / ethyl acetate solution of polymer acrylate resin, 160 parts by weight “Unidic” V-6850 DIC Corporation Solid content: 50% by mass “Unidic” V-6850 DIC Corporation Solid content: 50% by mass Resin precursor B: Urethane acrylate oligomer (“Shiko” UV3200B manufactured by Nippon Gosei Kagaku Kogyo Co., Ltd. Solid content concentration 100% by mass) 20 parts by mass Leveling agent “Futergent” 212M (manufactured by Neos Co., Ltd.) Solid content concentration 100% by mass 5 parts by mass α-Hydroxyacetophenone type photopolymerization initiator 3.0 parts by mass (“Irgacure” (registered trademark) 184 manufactured by BASF Japan Ltd.).

[0143] [Coating composition 13 for resin layer] The following materials were mixed and diluted with methyl ethyl ketone to obtain a resin layer coating composition 13 having a solids concentration of 20 mass %. Polyfunctional acrylate monomer 100 parts by weight “KAYARAD” (registered trademark) PET30, manufactured by Nippon Kayaku Co., Ltd., solid content concentration 100% by mass Leveling agent (LINC-5A manufactured by Kyoeisha Chemical Co., Ltd. Solid content concentration 100% by mass) 1 part by mass α-Hydroxyacetophenone type photopolymerization initiator 3.0 parts by mass (“Irgacure” (registered trademark) 184 manufactured by BASF Japan Ltd.).

[0144] [Coating composition 14 for resin layer] The following materials were mixed and diluted with methyl ethyl ketone to obtain a resin layer coating composition 14 having a solids concentration of 20% by mass. Resin precursor A: 80 parts by mass of urethane acrylate oligomer A1 Resin precursor B: 20 ​​parts by mass of urethane acrylate oligomer B1 Leveling agent “Futergent” 212M (manufactured by Neos Co., Ltd.) Solid content concentration 100% by mass 1 part by mass α-Hydroxyacetophenone type photopolymerization initiator 3.0 parts by mass (“Irgacure” (registered trademark) 184 manufactured by BASF Japan Ltd.).

[0145] The synthesis method of the urethane acrylate oligomer A1 is as follows. 108 parts by mass of bisphenol A diepoxy resin (YD-8125, manufactured by Nippon Steel Chemical Co., Ltd.), 45 parts by mass of acrylic acid as a (meth)acrylic acid derivative, 0.2 parts by mass of hydroquinone monomethyl ether as a polymerization inhibitor, and 0.8 parts by mass of dimethylaminoethyl methacrylate as a catalyst were added, and the mixture was heated to 95°C with stirring, and the reaction was continued for 14 hours while maintaining the temperature at 95°C. When the acid value became 1 mgKOH / g or less, the first stage reaction was terminated, and an epoxy acrylate having two hydroxyl groups was obtained.

[0146] Next, after lowering the temperature to 60°C, ethyl acetate was added as a dilution solvent, 0.03 parts by mass of di-n-butyltin dilaurate was added as a catalyst, and 83 parts by mass of dicyclohexylmethane diisocyanate was added dropwise over 2 hours while stirring, followed by 94 parts by mass of pentaerythritol triacrylate being added dropwise over 1 hour. After the dropwise addition, the reaction was continued for 5 hours to obtain urethane acrylate oligomer A1 having five functional groups and a weight average molecular weight of 1200.

[0147] The synthesis method of urethane acrylate oligomer B1 is as follows: 70 parts by mass of polytetramethylene glycol (PTMG1000 manufactured by Mitsubishi Chemical Corporation), 33 parts by mass of polyoxyethylene bisphenol A ether (Newpol BPE-40 manufactured by Sanyo Chemical Industries, Ltd.), and ethyl acetate were added and heated to an internal temperature of 60° C. 0.03 parts by mass of di-n-butyltin dilaurate was added as a synthesis catalyst, and 31 parts by mass of isophorone diisocyanate was added dropwise over 1 hour with stirring, and the reaction was continued for 2 hours after the end of the dropwise addition.

[0148] Then, 2.4 parts by mass of 2-hydroxyethyl acrylate was added dropwise over 1 hour. After the addition, the reaction was continued for 5 hours to obtain a bifunctional urethane acrylate oligomer B1 having a weight average molecular weight of 14,000.

[0149] [Coating composition 15 for resin layer] The following materials were mixed and diluted with methyl ethyl ketone to obtain a resin layer coating composition 15 having a solids concentration of 20% by mass. Resin precursor A: 60 parts by mass of urethane acrylate oligomer A1 Resin precursor B: 40 parts by mass of urethane acrylate oligomer B1 Leveling agent “Futergent” 212M (manufactured by Neos Co., Ltd.) Solid content concentration 100% by mass 1 part by mass α-Hydroxyacetophenone type photopolymerization initiator 3.0 parts by mass (“Irgacure” (registered trademark) 184 manufactured by BASF Japan Ltd.).

[0150] [Coating composition 16 for resin layer] The following materials were mixed and diluted with methyl ethyl ketone to obtain a resin layer coating composition 16 having a solids concentration of 20% by mass. Resin precursor A: 80 parts by mass of urethane acrylate oligomer A1 Resin precursor B: 20 ​​parts by mass of urethane acrylate oligomer B2 Leveling agent “Futergent” 212M (manufactured by Neos Co., Ltd.) Solid content concentration 100% by mass 1 part by mass α-Hydroxyacetophenone type photopolymerization initiator 3.0 parts by mass (“Irgacure” (registered trademark) 184 manufactured by BASF Japan Ltd.).

[0151] The synthesis method of resin precursor B2 is as follows: 70 parts by mass of polytetramethylene glycol (PTMG1000 manufactured by Mitsubishi Chemical Corporation), 33 parts by mass of polyoxyethylene bisphenol A ether (Newpol BPE-40 manufactured by Sanyo Chemical Industries, Ltd.), and ethyl acetate were added and heated to an internal temperature of 60° C. 0.03 parts by mass of di-n-butyltin dilaurate was added as a synthesis catalyst, and 31 parts by mass of isophorone diisocyanate was added dropwise over 1 hour with stirring, and the reaction was continued for 2 hours after the end of the dropwise addition.

[0152] Then, 1.2 parts by mass of 2-hydroxyethyl acrylate and 3.0 parts by mass of pentaerythritol triacrylate were added dropwise over 1 hour. After the addition, the reaction was continued for 5 hours to obtain a tetrafunctional urethane acrylate oligomer B2 solution having a weight average molecular weight of 15,000 as a resin precursor B.

[0153] [Coating composition 17 for resin layer] The following materials were mixed and diluted with methyl ethyl ketone to obtain a resin layer coating composition 17 having a solids concentration of 20 mass %. Resin precursor A: urethane acrylate oligomer 80 parts by mass (EBCRYL3701 Daicel Allnex Co., Ltd.) Resin precursor B: Urethane acrylate oligomer B1 20 parts by mass Leveling agent “Futergent” 212M (manufactured by Neos Co., Ltd.) Solid content concentration 100% by mass 1 part by mass α-Hydroxyacetophenone type photopolymerization initiator 3.0 parts by mass (“Irgacure” (registered trademark) 184 manufactured by BASF Japan Ltd.).

[0154] [Preparation of Support Substrates 1 to 4 with Release Layers] Using the above-mentioned coating composition for the release layer and the supporting substrate, a release layer was formed by the following method, and a supporting substrate with a release layer was prepared. The combination of the coating composition for the release layer, the method for forming the release layer, and the thickness of the release layer used is as shown in Table 1.

[0155] [Method 1 for forming release layer] Using a coating device with a small diameter gravure coater, the release layer coating composition was applied to a 50 μm thick polyester film (manufactured by Toray Industries, Inc., under the trade name "Lumilar" (registered trademark) R75X) by adjusting the gravure line frequency, peripheral speed, and solids concentration so as to obtain the release layer thickness shown in Table 1. The coating composition was then dried and cured by holding the film at a hot air temperature of 140°C for 30 seconds, thereby obtaining a support substrate 1 with a release layer.

[0156] [Method 2 for forming release layer] Using a coating device with a small diameter gravure coater, release layer coating compositions 2, 3 and 4 were applied to a 50 μm thick polyester film (manufactured by Toray Industries, Inc., under the trade name "Lumilar" (registered trademark) R75X) by adjusting the gravure line frequency, peripheral speed and solids concentration so as to obtain the release layer thicknesses listed in Table 1, and then the film was dried and cured by holding it at a hot air temperature of 120°C for 30 seconds to obtain support substrates with release layers 2 to 4.

[0157] [Method 3 for forming release layer] Using a coating device with a small-diameter gravure coater, the release layer coating composition was applied to a 40 μm thick triacetyl cellulose film (TD40UL, manufactured by Fujifilm Corporation) by adjusting the gravure line count, peripheral speed, and solids concentration so as to obtain the release layer thickness listed in Table 1, and then the film was dried and cured by holding it at a hot air temperature of 140°C for 30 seconds to obtain a support substrate 5 with a release layer.

[0158] [Create laminate] A resin layer was formed using the above-mentioned coating composition for the resin layer and the support substrate with a release layer to prepare a laminate. The combination of the coating composition for the resin layer, the method for forming the resin layer, and the thickness of the resin layer is as shown in Table 1.

[0159] [Method of forming resin layer] Using a continuous coating device having a single-layer slot die coater, the aforementioned resin layer coating composition was applied to the aforementioned support substrate with a release layer by adjusting the discharge flow rate from the slot so as to obtain the resin layer thickness shown in Table 1, and then the substrate was dried by holding the substrate at a hot air temperature of 80°C for 30 seconds, and then dried under an oxygen partial pressure of 0.1% by volume or less and an irradiation output of 400 W / cm. 2 , irradiation intensity is 120mJ / cm 2 The resin was cured by irradiating it with a high pressure mercury lamp under conditions such that

[0160] By the above-mentioned methods, the laminates were prepared in Examples 1 to 17 and Comparative Examples 1 to 4. The preparation method of the laminates and the thickness of the resin layer corresponding to each of the Examples and Comparative Examples are shown in Table 1.

[0161] [Table 1]

[0162] [Resin film formation 1] The support substrate with the release layer was peeled off from the laminate produced in Example 1 to obtain a resin film 1.

[0163] [Formation of resin film 2] The support substrate with the release layer was peeled off from the laminate produced in Example 2 to obtain a resin film 2.

[0164] [Formation of resin film 3] The support substrate with the release layer was peeled off from the laminate produced in Example 3 to obtain a resin film 3.

[0165] [Formation of resin film 4] The support substrate with the release layer was peeled off from the laminate produced in Example 4 to obtain a resin film 4.

[0166] [Formation of resin film 5] The support substrate with the release layer was peeled off from the laminate produced in Example 5 to obtain a resin film 5.

[0167] [Formation of resin film 6] The support substrate with the release layer was peeled off from the laminate produced in Example 6 to obtain a resin film 6.

[0168] [Formation of resin film 7] The support substrate with the release layer was peeled off from the laminate produced in Example 7 to obtain a resin film 7.

[0169] [Formation of resin film 8] The support substrate with the release layer was peeled off from the laminate produced in Example 8 to obtain a resin film 8.

[0170] [Formation of resin film 9] The support substrate with the release layer was peeled off from the laminate produced in Example 9 to obtain a resin film 9.

[0171] [Formation of resin film 10] The support substrate with the release layer was peeled off from the laminate produced in Example 10 to obtain a resin film 10.

[0172] [Formation of resin film 11] The support substrate with the release layer was peeled off from the laminate produced in Example 11 to obtain a resin film 11.

[0173] [Formation of resin film 12] The support substrate with the release layer was peeled off from the laminate produced in Example 12 to obtain a resin film 12.

[0174] [Formation of resin film 13] The support substrate with the release layer was peeled off from the laminate produced in Example 13 to obtain a resin film 13.

[0175] [Formation of resin film 14] The support substrate with the release layer was peeled off from the laminate produced in Example 14 to obtain a resin film 14.

[0176] [Formation of resin film 15] The support substrate with the release layer was peeled off from the laminate produced in Example 15 to obtain a resin film 15.

[0177] [Formation of resin film 16] The support substrate with the release layer was peeled off from the laminate produced in Example 16 to obtain a resin film 16.

[0178] [Formation of resin film 17] The support substrate with the release layer was peeled off from the laminate produced in Example 17 to obtain a resin film 17.

[0179] By the above-mentioned method, the resin films were prepared in Examples 18 to 2634. The method for forming the resin film and the thickness of the resin film corresponding to each Example are shown in Table 2.

[0180] [Table 2]

[0181] [Evaluation of physical properties of laminates and resin films] The laminates produced in Examples 1 to 17 and Comparative Examples 1 to 4 and the resin films produced in Examples 18 to 34 were evaluated for physical properties as shown below, and the results obtained are summarized in Tables 3 and 4. Unless otherwise specified, measurements were performed three times at different locations for one sample in each Example and Comparative Example, and the average value was used. Furthermore, the presence or absence of resin components represented by Chemical Formulas 1 to 3 calculated based on the results of the physical property evaluation is listed in Tables 3 and 4.

[0182] [Table 3]

[0183] [Table 4]

[0184] [Elastic modulus distribution of resin layer and resin film surface] The elastic modulus distribution of the resin layer and the resin film surface was measured using an AFM (DimensionIcon manufactured by Burker Corporation) in PeakForceQNM mode. The elastic modulus distribution was calculated from the obtained force curve using the attached analysis software "NanoScopeAnalysis V1.40" based on the JKR contact theory.

[0185] Specifically, following the PeakForceQNM mode manual, the cantilever's warpage sensitivity, spring constant, and tip curvature were configured, and measurements were performed under the following conditions, and the resulting DMT Modulus channel data was used as the elastic modulus of surface B. Note that although the spring constant and tip curvature vary depending on the individual cantilever, a cantilever that satisfies the conditions of a spring constant of 0.3 (N / m) to 0.5 (N / m) and a tip curvature radius of 15 (nm) or less was adopted and used for the measurement, as this is within the range that does not affect the measurement. The measurement conditions are shown below. Measurement equipment: Atomic force microscope (AFM) manufactured by Burker Corporation Measurement mode: PeakForceQNM (force curve method) Cantilever: Bruker AXS SCANASYST-AIR (Material: Si, spring constant K: 0.4 (N / m), tip curvature radius R: 2 (nm)) Measurement atmosphere: 23℃ in air Measurement range: 5 (μm) square Resolution: 512×512 Cantilever movement speed: 10(μm / s) Maximum pressing load: 10(nN).

[0186] [Elastic modulus of region A E A , elastic modulus E of region B B and the difference (E A -E B )] The data of the DMT Modulus channel obtained was then analyzed using the analysis software "NanoScopeAnalysis V1.40". First, the Number Histogram Bins (number of classes) was set to 3,000 points in Depth mode, and the frequency histogram of the elastic modulus (horizontal axis - elastic modulus (MPa), vertical axis - frequency (%)) was calculated. The number of peaks was then determined for the frequency histogram of the elastic modulus obtained using the following method. Here, a peak means a maximum value of frequency, and when the frequency histogram of the elastic modulus has only one maximum value, that maximum value is the peak, and when the volume-based frequency distribution has two or more maximum values, the maximum value with a frequency difference of 2% or more from the minimum value present between the target maximum values ​​is treated as the peak. The number of peaks was determined for the frequency histogram of the elastic modulus obtained based on this criterion.

[0187] Next, the elastic modulus corresponding to the peak determined above is read from the frequency histogram of the elastic modulus, and the maximum one is the elastic modulus E of region A. A Then, calculate the product of the elastic modulus x and the frequency F(x) at each point of the remaining peaks, and divide the sum ΣxF(x) by the sum ΣF(x) of the frequencies to obtain an average value weighted by the frequency. This value is the elastic modulus E of region B. B In addition, when only one applicable peak exists, it is determined that region B does not exist, and the physical properties of region B are not applicable.

[0188] [Average number of pieces in area B] The number of regions B was calculated using the elastic modulus distribution obtained above. First, the obtained image was smoothed using the analysis software "NanoScopeAnalysis V1.40" under the condition of Plane Fit (XY, 3rd), and then the contrast was adjusted using Image Color Scale Adjust (Autoscale). Next, the image was converted to grayscale using the image processing software EasyAccess Ver6.7.1.23, the white balance was adjusted so that the brightest and darkest parts were within an 8-bit tone curve, and the contrast was adjusted so that the boundaries of the regions were clearly distinguishable. Next, the image analysis software ImageJ 1.45s (developed by: National Institutes of Health (NIH)) was used to binarize the pixels at the aforementioned boundaries, and each region was analyzed using Particle Analyze (Include holes: Yes, Size: 0-Infinty). The total number of data displayed in the Results window was the number of regions B contained within a range of 5 μm × 5 μm. Similar measurements and analyses were repeated at five locations, and the average value was used as the average number of regions B.

[0189] [Major axis radius of area B] Next, the image analysis software ImageJ 1.45s (developed by the National Institutes of Health (NIH)) was used to analyze the major axis radius by Particle Analyze (Include holes: Yes, Size: 0-Infinty). Specifically, Fit Ellipse was selected from Set Measurements, and the average value of Major displayed in the Results window was used as the major axis radius.

[0190] [Surface composition of resin layer and resin film] Using a time-of-flight secondary ion mass spectrometer TOF-SIMS V manufactured by ION TOF and its measurement software SURFACE LAB 6, the mass distribution of positive and negative ions was measured by secondary ion mass spectrometry in a range of 5 nm from the outermost surface of the resin layer and resin film under the following conditions. Measurement conditions Primary ion species: Bi3++ Primary ion current: 1.000pA Accelerating voltage: 25kV Measurement range: 100μm×100μm Resolution: 128×128 Number of scans: 36.

[0191] First, a mass distribution analysis was performed on the obtained data. It was determined that when the mass distribution contains negative ions with mass number 85 or negative ions with mass number 71, the resin component represented by chemical formula 1 is present; when it contains positive ions with mass number 69 (chemical formula 4) and positive ions with mass number 169 (chemical formula 5) at the same time, the resin component represented by chemical formula 2 is present; and when it contains positive ions with mass number 45 or positive ions with mass number 59, the resin component represented by chemical formula 3 is present.

[0192] At this time, an Ar gas cluster sputtering gun was used for cutting in the depth direction. The thickness of the resin layer and the resin film of the laminate was measured in advance to determine the sputtering rate. Then, the sample with a known resin layer thickness was cut to the support substrate side, and the cutting rate per unit time was calculated. From this, the time required to cut 5 nm was calculated, and the integrated result of this time was adopted as the analysis result for the range of 5 nm from the outermost surface of the resin layer and the resin film.

[0193] Next, an analysis of the spatial distribution was performed. An image of the spatial distribution of the outermost surface was reconstructed from the data measured above. At this time, when negative ions with mass numbers of 85 or 71, positive ions with mass numbers of 150 (chemical formula 4), positive ions with mass numbers of 393 (chemical formula 5), ​​positive ions with mass numbers of 45, and positive ions with mass numbers of 59 were detected, the analysis conditions were adjusted to the polarity and mass of the ions of interest, and analysis was performed.

[0194] Specifically, first, using software built into the secondary ion mass spectrometer, two-dimensional position information on the outermost surface of the resin layer and secondary ion intensity information of each fragment ion at the corresponding positions were extracted.

[0195] The standard deviation of the secondary ion intensity can be calculated based on the extracted secondary ion intensity value. The spatial distribution obtained was analyzed in the same manner as the elastic modulus distribution, the average number was calculated, and if the difference from the elastic modulus distribution was less than ±5%, it was determined that the same domain was formed.

[0196] [Evaluation of laminate and resin layer properties] The laminate and the resin layer were subjected to the following characteristic evaluations, and the results are shown in Table 5. Unless otherwise specified, the measurements were performed three times for one sample in each Example and Comparative Example at different locations, and the average values ​​were calculated and rounded off to the first decimal place.

[0197] [Table 5]

[0198] [Evaluation of scratch resistance of resin layer surface] The laminates produced in Examples 1 to 17 and Comparative Examples 1 to 4 were subjected to a load of 250 kg / cm using #0000 steel wool and a flat surface abrasion tester (DAIE KAGAKU SEIKI SEISAKUSHO CO., LTD., PA-300A). 2 The surface of the resin layer was rubbed back and forth 10 times with this, and the presence or absence of scratches was visually observed and judged according to the following criteria, with a score of 4 or more being considered a pass. 10 points: 0 7 points: 1 or more, less than 5 4 points: 5 or more, but less than 10 1 point: 10 or more. [Evaluation of peelability of resin layer] For the laminates produced in Examples 1 to 17 and Comparative Examples 1 to 4, one side of an adhesive film (Panac Corporation, Panaclean PD-S1, 25 μm product) from which the separator had been removed was attached to the surface of the resin layer of the laminate while taking care not to trap air bubbles, and then the separator was peeled off from the adhesive film, and a PET film (188 μm, Toray Industries, Inc., "Lumirror" (registered trademark) T60) was attached.

[0199] The supporting substrate and the resin layer were previously peeled slightly from one end, and the peeled resin layer was peeled in a 180 degree direction and judged according to the following criteria, with an average score of 4 or more being considered a pass. 10 points: The film can be peeled off uniformly even at a peel speed of 10,000 mm / min. 7 points: At a peel speed of 10,000 mm / min, the film could not be peeled off uniformly within the surface, but at a peel speed of 1,000 mm / min, the film could be peeled off uniformly within the surface. 4 points: At a peel speed of 1,000 mm / min, the film could not be peeled off uniformly within the surface, but at a peel speed of 300 mm / min, the film could be peeled off uniformly within the surface. 1 point: Unable to peel evenly across the surface at 300 mm / min.

[0200] [Evaluation of resin layer quality] The laminates produced in Examples 1 to 17 and Comparative Examples 1 to 4 were subjected to a 100m 2 The samples were visually inspected, and the number of samples with deformations (cracking, foreign matter) of 1 mm or more in diameter was judged according to the following criteria, with an average score of 4 or more being considered a pass. 10 points: 1 or less 7 points: 2 or more and 5 or less 4 points: 6 or more and 10 or less 1 point: 11 or more.

[0201] [Evaluation of shape conformity of resin layer] For the laminates produced in Examples 1 to 17 and Comparative Examples 1 to 4, one side of an adhesive film (Panac Corporation, Panaclean PD-S1 25 μm product) from which the separator had been removed was attached to the surface of the resin layer of the laminate, taking care not to introduce air bubbles, and then cut into a rectangle 90 mm wide x 90 mm long in a manner that would not cause cracks at the edges. The separator on the other side was peeled off and the film was attached to a cylinder with a diameter of 30 mm. The condition of the resin layer at this point was observed and judged according to the following criteria, with an average score of 4 or more being considered a pass. 10 points: The resin layer can be applied evenly without cracking or peeling. 7 points: Fine cracks are visible at the edges of the resin layer, but otherwise the adhesive can be applied evenly. 4 points: Fine cracks are visible at the edges and center of the resin layer, but otherwise the adhesive can be applied evenly. 1 point: There is a crack or a gap in the center of the resin layer, making it impossible to apply evenly.

[0202] [Crack resistance of resin layer] For the laminates produced in Examples 1 to 17 and Comparative Examples 1 to 4, one side of an adhesive film (Panac Corporation, Panaclean PD-S1, 25 μm product) from which the separator had been removed was attached to the surface of the resin layer of the laminate while taking care not to trap air bubbles, and holes were made with a 6 mm diameter hole punch for documents. Then, the separator on the other side of the adhesive layer was peeled off, and the laminate was attached to glass.

[0203] After leaving the sample in an environment of 23°C and 50% humidity for 48 hours, the area around the hole was observed and judged according to the following criteria, with an average score of 4 or more being considered a pass. 10 points: No cracks or chips around the hole in the resin layer 7 points: There are chips around the hole in the resin layer, but no cracks. 4 points: Cracks less than 0.5 mm from the edge of the hole are found around the resin layer. 1 point: Cracks are found around the hole in the resin layer, extending 0.5 mm or more from the edge of the hole. [Evaluation of resin layer lifting] The laminates produced in Examples 1 to 17 and Comparative Examples 1 to 4 were cut with a cutter knife into 100 x 200 mm squares and wrapped around a cylinder with a diameter of 30 mm. The edges of the cut sections were observed and judged according to the following criteria, with an average score of 4 or more being considered a pass. 10 points: There is no lifting at either end when cut with a utility knife or when wrapped around a cylinder. 7 points: The ends do not float when cut with a utility knife, but there is a slight amount of floating at the ends when wrapped around a cylinder. 4 points: The end portion is slightly raised when cut with a utility knife, and is slightly raised when wrapped around a cylinder. 1 point: When cut with a utility knife, the end floats, and when wrapped around a cylinder, the entire end floats. [Explanation of symbols]

[0204] 1,6,12,20,26,33 : Laminated body 2,7,13,21,27,34: Release film 3,8,14,19,22,28,35 : Supporting base material 4,9,10,15,23,29,36 : Release layer 5,11,16,24,30,37: Resin layer 17: Protective film 18: Adhesive layer 25: Functional layer 31: Sea-island region B (island side) 32: Island area A (sea side) 38: Region B of lamellar structure 39: Region A of lamellar structure [Industrial Applicability]

[0205] The resin film and laminate of the present invention have excellent scratch resistance, transportability as a thin film, and conformability to surface shapes, and can be suitably used for moldings such as plastics and metals, taking advantage of the advantages of being able to transfer layers having functions such as weather resistance, gas barrier properties, and anti-blocking properties.

[0206] To name a few examples, it can be suitably used for the surface materials, internal materials, constituent materials, and manufacturing process materials of plastic molded products such as glasses / sunglasses, cosmetic cases, and food containers, aquariums, showcases for exhibitions, smartphone housings, touch panels, color filters, flat panel displays, flexible displays, flexible devices, wearable devices, sensors, circuit materials, electrical and electronic applications, home appliances such as keyboards, remote controls for televisions and air conditioners, mirrors, window glass, buildings, dashboards, car navigation touch panels, vehicle parts such as rearview mirrors and windows, and various printed matter, medical films, films for sanitary materials, medical films, agricultural films, and building materials.

Claims

1. A method for producing a laminate having a release layer and a resin layer in this order from the supporting substrate side on at least one surface of the supporting substrate, comprising: The method for producing the laminate includes applying a coating composition for a resin layer onto a release layer of a supporting substrate, and then drying and curing the coating composition to form a resin layer, The coating composition for the resin layer contains two types of resin precursors, and a resin component represented by Chemical Formula 2 and / or a resin component represented by Chemical Formula 3, In the coating composition for resin layer, when the total content of the resin precursors is 100 parts by mass, the content of the resin component represented by Chemical Formula 2 and / or the resin component represented by Chemical Formula 3 is 0.3 to 3.0 parts by mass, When observed by an atomic force microscope, a region (referred to as region B) having a lower elastic modulus than a region (referred to as region A) having a higher elastic modulus is present on the surface of the resin layer, and within a range of 5 nm from the surface of the resin layer, the region A contains a resin component represented by Chemical Formula 1, The method for producing a laminate, wherein the laminate satisfies the following conditions: Condition 1: Elastic modulus E of region B B is 1,500 MPa or less Condition 2: The average number of regions B in a 5 μm square is 50 to 300. 【Chemistry 1】 【Chemistry 2】 【Chemistry 3】 R 1 is hydrogen or a methyl group, R 2 , R 3 , R 4 is any one of the following (i) to (vi): (i) a substituted or unsubstituted alkylene group (ii) a substituted or unsubstituted arylene group (iii) a substituted alkylene group having an ether group, an ester group, or an amide group therein (iv) an unsubstituted alkylene group having an ether group, an ester group, or an amide group therein (v) a substituted arylene group having an ether group, an ester group, or an amide group therein (vi) an unsubstituted arylene group having an ether group, an ester group or an amide group therein

2. 2. The method for producing a laminate according to claim 1, wherein each of the two types of resin precursors corresponds to any one of a polyfunctional (meth)acrylate monomer, a (meth)acrylate oligomer, an alkoxysilane having a (meth)acrylic group, an alkoxysilane hydrolysate having a (meth)acrylic group, an alkoxysilane oligomer having a (meth)acrylic group, an acrylic polymer having a (meth)acrylic group, a urethane polymer having a (meth)acrylic group, an epoxy polymer having a (meth)acrylic group, and a silicone polymer having a (meth)acrylic group.

3. The method for producing a laminate according to claim 1 or 2, which is used for an application in which the resin layer is attached to an adherend and the supporting substrate is peeled off from the resin layer.

4. The method for producing a laminate according to any one of claims 1 to 3, characterized in that the following conditions are satisfied: Condition 3: Elastic modulus E of the region A A and the elastic modulus E of the region B B The difference between A -E B ) is 100 MPa or more. Condition 4: the major axis radius of the region B is 25 nm or more and 250 nm or less

Citation Information

Patent Citations

  • Fluorine-containing surface active oligomer, and preparation method and ultraviolet light cured anti-fogging coating thereof

    CN105482067A

  • Transfer sheet

    JP2004034385A

  • Transfer film

    JP2014104705A

  • Peel-strength-adjustable hard coat transfer film and method for manufacturing the same

    JP2014180809A

  • Transfer foil

    JP2017065017A